Kesulitan Menyelesaikan Soal Cerita Pola Bilangan Berdasarkan Langkah Polya Siswa Kelas VIII SMPN 2 Bukittinggi Tahun Pelajaran 2022/2023 - Nofriadi, Fauzan; Rahmad, Tasnim; Rusdi, Rusdi; Fitri, Haida (Lembaga Intelektual Muda (LIM) Maluku, 2024)
This research was motivated by students who experienced difficulties in solving number pattern story problems in grade VIII of SMPN 2 Bukittinggi. This study aims to find out the difficulties of students in solving number pattern story problems in grade VIII students of SMPN 2 Bukittinggi. This type of research is quantitative descriptive research, Sampling in this study uses a purposive sampling technique, namely the determination of research subjects with certain considerations. The sample in this study is 30 students. This research is in the form of an essay test question about number patterns distributed to students who research samples are. The results of this study show that the difficulties experienced by students with each polya indicator are that there are still many students who have difficulty being able to solve story problems, the difficulties that researchers can see include difficulties in understanding the problem 83%, difficulty in compiling a plan 16%, implementing the plan 93% and re-examining the solutions obtained 16%.